Efficacy of Garlic Tablet to Control Seed-Borne Fungal Pathogens of Cucumber - Amin, ABM Ruhul; Rashid, MM; Meah, MB (Journal of Agriculture & Rural Development, 2010)
An experiment was conducted to find out the efficacy of garlic tablets in controlling seed-borne fungal pathogens of cucumber. Suspention of garlic tablet was prepared in water at the concentrations of 1:3, 1:4, 1:5 and 1:6. Seeds of cucumber were treated with the suspentions for 15 minutes. Seeds under control were treated with plain water. Seven fungal pathogens, namely Aspergillus flavus, Aspergillus niger, Fusarium oxysporum, Fusarium moniliforme, Penicillium spp., Doratomycetes sp. and Rhizopus stolonifer were found to be associated with the cucumber seeds. Their prevalence ranged from 1.0-8.0, 1.0-4.0, 1.0-15.0, 1.0-8.0, 0.0-9.0, 1.0-17.0 and 0.0-12.0% respectively under different treatments including control. All concentrations of the material caused significant decrease in the prevalence of seed-bornefungi, occurrence of abnormal seedlings and rotten seeds as compared to control. On the other hand, germination increased over control due to seed treatment with garlic tablet. The higher increase in germination and reduction in occurrence of seed-borne fungi, rotten seed and abnormal seedling were corroborated with higher doses of garlic tablet. Key words: Garlic tablet; cucumber seed; seed treatment; fungal pathogens; control. DOI: 10.3329/jard.v7i1.4433 J Agric Rural Dev 7(1&2), 135-138, June 2009